Peningkatan dan Optimalisasi Kesehatan Lansia di Masa Pandemi Covid-19 di Binjai melalui Gerakan 3M - Nurman Achmad (Universitas Medan Area, 2022)
Covid-19 or SARS-CoV-2 is a virus that emerged at the end of 2019 and has never been identified in the human body before. According to the World Health Organization (WHO), this virus is vulnerable to attack the elderly who have high mortality and morbidity in the face of the Covid-19 pandemic. In this case, of course, the elderly really need access to intense health services, especially for the elderly who have a history of chronic or degenerative diseases. One of the efforts that can be done is such as maintaining cleanliness through the 3M Movement, namely washing hands, wearing masks and diligently consuming herbal herbs. Binjai City is one of the regencies that are included in the five regencies that have the largest elderly population in North Sumatra. Therefore, it is necessary to optimize empowerment in these districts to improve the quality of life of the elderly during the Covid-19 pandemic. The implementation method in this empowerment activity is through socialization and practice. With this activity, the participants understood how to maintain cleanliness and health and started implementing the 3M Movement.